1999
DOI: 10.1175/1520-0477(1999)080<2299:dasvot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Variations of the Rainfall Measured by the Automatic Rainfall and Meteorological Telemetry System in Taiwan

Abstract: Under a weather hazard prevention program in Taiwan, the Vaisala Meteorological Instrument, Inc., of Finland and the Environmental Science and Engineering Corporation of Taiwan jointly developed and installed more than 300 stations of the Automatic Rainfall and Meteorological Telemetry System (ARMTS) over this subtropical island with an area of approximately 30 000 km 2. The Taiwan ARMTS network can provide the hourly rainfall data of not only a densely instrumented, but also very uniquely observed, geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 21 publications
11
93
0
Order By: Relevance
“…The NSC site (full names are listed in Table 2) is located on a subtropical island and is subjected to heavy rainfall. EOP3 observations reveal that the maximum rainfall hour at this site is 1700-1900 LST, which is similar to the findings (1600-1700 LST) of Chen et al (1999) based on more than 300 stations and the findings (1700 LST) of Kishtawal and Krishnamurti (2001) based on Tropical Rainfall Measuring Mission (TRMM) data. At the HIM site, EOP3 data reveal that the maximum precipitation hour is 2300 LST; the same result was also reported by Tartari et al (1998) and Ueno et al (2001) for nearby stations and Hirose and Nakamura (2005) for a station located south of Mt.…”
Section: Diurnal Cycle Of Precipitation In Gcmssupporting
confidence: 82%
“…The NSC site (full names are listed in Table 2) is located on a subtropical island and is subjected to heavy rainfall. EOP3 observations reveal that the maximum rainfall hour at this site is 1700-1900 LST, which is similar to the findings (1600-1700 LST) of Chen et al (1999) based on more than 300 stations and the findings (1700 LST) of Kishtawal and Krishnamurti (2001) based on Tropical Rainfall Measuring Mission (TRMM) data. At the HIM site, EOP3 data reveal that the maximum precipitation hour is 2300 LST; the same result was also reported by Tartari et al (1998) and Ueno et al (2001) for nearby stations and Hirose and Nakamura (2005) for a station located south of Mt.…”
Section: Diurnal Cycle Of Precipitation In Gcmssupporting
confidence: 82%
“…For the first event (9 August 1999), up to 393 mm fell over the slopes in southwestern Taiwan, while in the second event (13 August 1994), up to 450 mm fell over the coastal and lowland areas of southwestern Taiwan. The European Center for Medium-Range Weather Forecasts/ Tropical Ocean-Global Atmosphere (EC/TOGA) data, rainfall data from the Automatic Rainfall and Meteorological Telemetry System (ARMTS, Chen et al 1999), conventional surface stations over Taiwan, and MM5 were employed to investigate the causes of heavy rainfall observed over the slopes and/or lowlands. The synoptic situation in both events showed that a low pressure belt extended from the east coast of China into the west Pacific south of Japan, and a monsoon trough stretched from southern China into the South China Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Gray and Jacobson, 1977;Chen et al, 2010), and convergence of surface wind and water vapor flux (e.g. Wai et al, 1996;Chen et al, 1999). Here, we propose that all these mechanisms have impacts on the formation of the early-morning maximum P SEC as well.…”
Section: Introductionmentioning
confidence: 62%
“…Such a feature also predominates in some areas east of 110 • E, including the middle and lower reaches of the Yangtze River, the North China Plain, and the coastal regions of China (Peacock, 1952;Chan and Ng, 1993;Yin et al, 2009;Chen et al, 2010). In contrast, the northern and southern parts of areas east of 110 • E are dominated by daytime precipitation (Chen et al, 1999Yu et al, 2007a). Because the diurnal rainfall over EA varies with a high geographical dependence, many previous studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation